The effect of financial development on the investment cash flow relationship: cross-country evidence from Europe - Bo Becker; Jagadeesh Sivadasan (European Central Bank (ECB), 2006)
We investigate financing constraints in a large cross-country data set covering most of the European economy. Firm level investment sensitivity to cash flow is used to identify financing constraints. We find that the sensitivities are significantly positive on average, controlling for country and industry fixed effects, as well as firm level controls. Most importantly, the cash flow sensitivity of investment is lower in countries with better-developed financial markets. This suggests that financial development may mitigate financial constraints. This effect is weaker in conglomerate subsidiaries, which are likely to have access to internal capital markets and depend less on the outside financial environment, and possibly for firms in industries with highly liquid assets as well. This result sheds light on the link between financial and economic development.
Keywords: E44; G31; L10; 330; Europe; financial constraints; Financial Development; Investment; Unternehmensfinanzierung; Cash Flow; Investitionsentscheidung; EU-Staaten; Europa